Le Corpus of Anglo-Saxon Stone Sculpture in England : Constitution, documentation numérique et enjeux - Celia Orsini; Sarah Semple (Les Cahiers de l'École du Louvre)
After almost half a century of research, the Corpus of Anglo-Saxon Stone Sculpture (CASSS) project, coordinated by Professor Rosemary Cramp, is coming to an end. It brings together inventories of all Anglo-Saxon sculptural remains dating from between the seventh and twelfth centuries. With the final publications in 2022, it will comprise over eighteen publications, sixteen of which are devoted to inventories from each county in England. The end of this colossal project is an opportunity to look back at the strengths and limitations of an operation built over the long term that has survived the great transformations brought about by the digital age.